Psocoptera em cavernas do Brasil: riqueza, composição e distribuição - Carmo, Thaís Oliveira do (2009)
The Order Psocoptera is widely distributed throughout the world, but there are few studies concerning this order, and such information is still scarce in Brazil. Furthermore, there is no specific work concerning the relations of these insects with the Brazilian cave environment. Therefore, to increase the knowledge about this order, this study aimed to verify which families and genera of Psocoptera are associated to Brazilian caves, where these insects are commonly found inside the caves, and if richness is influenced by the lithology of the caves or the biome in which they are found. For that, 192 caves were sampled in 70 municipalities of fifteen Brazilian states, located in the Caatinga, the Cerrado and Mata Atlântica biomes. A total of 148 species belonging to 38 genera were identified, distributed in 21 families. New records for families and genera of the order Psocoptera in the country and in caves were found in this work. The families Prionoglarididae and Trichopsocidae were recorded for the first time in Brazil. Sixteen genera of other families also had their first record in the country, and eleven genera and 29 families had their first record in caves. Furthermore, a new genus (belonging to Prionoglarididae) and 21 new species (belonging to Prionoglarididae and Psyllipsocidae) were found. These insects were collected in the entire extension of the caves, but most were found near the entrances, which reinforce their importance as components of the para-epigean communities. Most of the collections occurred in the Cerrado and limestone caves. The type of rock forming the caves and the biome where it is inserted had shown no influence in the richness of psocids found in caves in the country. Since this study is the first concerning the families and genera of Psocoptera associated with cave environments in Brazil, many of the presented information are important records of organisms of this order not only in caves, but also in the country.